2022
DOI: 10.3390/ijerph191912021
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nitrate Intake on Recovery from Exercise-Related Fatigue: A Systematic Review

Abstract: Background: Recovery between efforts is critical to achieving optimal physical and sports performance. In this sense, many nutritional supplements that have been proven to improve recovery and physical and physiological performance are widely used. Supplements such as nitrates (NO3−), including organic foods such as beets, promote muscle recovery and relieve fatigue. This study aimed to comprehensively summarise the available literature on the effect of NO3− consumption on exercise-related fatigue and muscle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…This is the first exercise-based human clinical trial to investigate the influence of BEET supplementation on inflammation using a human systems biology approach. Other similar studies used a few targeted outcomes, had widely disparate research designs, and generally reported null or minor effects of increased plasma NO 3 − + NO 2 − from nitrate supplementation on post-exercise inflammation biomarkers including cytokines ( 8 , 17–19 ). In one study with 34 runners, beetroot juice versus placebo supplementation for 3 days following a marathon race had no effect on muscle soreness, creatine kinase, interleukin (IL)-6, IL-8, tumor necrosis factor-α (TNFα), blood leukocyte cell counts, or C-reactive protein (CRP) ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first exercise-based human clinical trial to investigate the influence of BEET supplementation on inflammation using a human systems biology approach. Other similar studies used a few targeted outcomes, had widely disparate research designs, and generally reported null or minor effects of increased plasma NO 3 − + NO 2 − from nitrate supplementation on post-exercise inflammation biomarkers including cytokines ( 8 , 17–19 ). In one study with 34 runners, beetroot juice versus placebo supplementation for 3 days following a marathon race had no effect on muscle soreness, creatine kinase, interleukin (IL)-6, IL-8, tumor necrosis factor-α (TNFα), blood leukocyte cell counts, or C-reactive protein (CRP) ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary performance benefit of nitrate supplementation appears to be a reduction in the energy cost of exercise and a corresponding modest improvement in endurance capacity ( 5–7 ). Studies reporting performance benefits used acute nitrate doses of 5–6 mmol (or about 300 mg), or chronic doses at about half that amount ( 8 ). Chronic nitrate supplementation has not been consistently linked to improvements in aerobic capacity or performance ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the proposed models are suitable for but not limited to the development of the PCS-based user interfaces. Fatigue in the field of sport training and physiology is widespread for researchers [91,92]. Both subjective and objective research methods are applied.…”
Section: Discussion On Performance In Assistive Systemsmentioning
confidence: 99%
“…Furthermore, impulse-response models in the physiological domain elegantly include fatigue factor in mathematical performance models. Although a mathematical impulse-response model abstracts the human performance to two factors (fitness and fatigue), it has still been validated in many studies regarding the performance estimation of athletes [91,92].…”
Section: Discussion On Performance In Assistive Systemsmentioning
confidence: 99%